2022
DOI: 10.1021/acs.energyfuels.1c03728
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Alteration during Low-Salinity Water Flooding

Abstract: Low-salinity water flooding (LSWF) for hydrocarbon recovery has attracted industrial attention, owing to its simplicity and economic feasibility. Although this topic has received numerous studies, mechanisms driving the low-salinity effect remain poorly understood. This study is aimed at investigating the direct effects of injecting lowsalinity brine (0.6 and 0.2 M NaCl) as the non-wetting fluid and Soltrol 130 as a synthetic wetting fluid on outcrop "Austin Chalk" rock samples. The petrophysical properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…71−76 This is further highlighted by the report of Al-Bayati et al 77 who described the changes in the carbonate rock samples and concluded that the observed recovery was caused by the electrical double layer effect brought on by the injected fluid's reduced ionic strength. Our findings further provide evidence to support the conclusions by Al-Bayati et al; 77 however, mineral dissolution as a governing mechanism is ruled out.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…71−76 This is further highlighted by the report of Al-Bayati et al 77 who described the changes in the carbonate rock samples and concluded that the observed recovery was caused by the electrical double layer effect brought on by the injected fluid's reduced ionic strength. Our findings further provide evidence to support the conclusions by Al-Bayati et al; 77 however, mineral dissolution as a governing mechanism is ruled out.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This lays the foundation for understanding the critical role the electrical double layer plays in the quest for mineral wettability control. Several mechanisms, including multivalent ionic exchange, electrical double layer (EDL) expansion, electrostatic bond interactions, surface charge alteration, and calcite dissolution, have been proposed in the literature to be responsible for the carbonate rock wettability. This is further highlighted by the report of Al-Bayati et al who described the changes in the carbonate rock samples and concluded that the observed recovery was caused by the electrical double layer effect brought on by the injected fluid’s reduced ionic strength. Our findings further provide evidence to support the conclusions by Al-Bayati et al; however, mineral dissolution as a governing mechanism is ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms the retention of surfactants on the surface of the rock pores. Moreover, the post-injection deionized water may have caused the mineral dissolution of the carbonate core [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multivalent ionic exchange, an EDL expansion, electrostatic bond interactions, surface charge alteration, and calcite dissolution are the wettability modification mechanisms connected with carbonate rocks. , This is highlighted in the report of Al-Bayati et al who described the change in the carbonate rock samples and concluded that the observed recovery was caused by the EDL effect brought on by the injected fluid’s reduced ionic strength. Thus, understanding the electrostatic interaction at the rock surface caused by the salinity and composition of the brine is necessary to understand these mechanisms.…”
Section: Wettability Alteration and The ζ-Potentialmentioning
confidence: 99%
“…The effect of both brines has gained significant attention recently and continues to be an active area of research. Several studies are available in the literature on smart and LSW effects on reservoir wettability and oil recovery. ,, For example, using AFM and contact angle and ζ-potential measurements, Al Maskari et al described the impact of pH (caused by mineral dissolution in LSW) on carbonate surface wettability. Findings indicated that the contact angle decreased as pH increased, and this observation was corroborated by an increase in magnitude of the negative surface charge under the same circumstances.…”
Section: Smart and Low Salinity Watermentioning
confidence: 99%